Patient-centeredness and endometriosis: Definition, measurement, and current status. (July 2018) - Geukens, E.I.; Apers, S.; Meuleman, C.; D'Hooghe, T.M.; Dancet, E.A.F.
Abstract: The patient-centeredness of care is important for health care quality, especially because it was recently associated with health-related quality of life, which is increasingly being recognized as the ultimate outcome parameter of health care. Therefore, insight into the definition, measurement, and current status of the patient-centeredness of clinics is important for all health care professionals caring for patients with endometriosis. The definition of patient-centered endometriosis care is based on research into the most common preferences, needs, and values of patients with endometriosis and can be summarized in ten dimensions. One valid and reliable questionnaire exists, the ENDOCARE questionnaire, which allows measuring the patient-centeredness status of an endometriosis clinic. This questionnaire has been used to benchmark centers in different countries and has allowed the identification of ten targets for improving the patient-centeredness of endometriosis care. The next step would be to use the ENDOCARE questionnaire before and after an improvement project.